Klasik Türk şiirinde askerî tabirler (başlangıçtan XVI. yüzyıl sonuna kadar) - Çaycıoğlu, Melike Kübra (My University, 2025)
Bu çalışmada klasik Türk şiirinin başlangıcından XVI. yüzyıl sonuna kadar olan seçilmiş divanlarda, askerî tabirlere dair kapsamlı bir araştırma yapılmıştır. Seçilen divanlardaki askerî tabirler, belirli bir tasnife tabi tutulmuş ve incelenmiştir. Divanlar seçilirken asker şairler ve yaşadığı devirde meşhur olan şairlerin divanları tercih edilmiştir. Türk milletinin kahramanlıklarla ve zaferlerle dolu askerî tarihine edebî manzum metinler referans gösterilerek değinilmiştir. Dört bölümden oluşan bu çalışmada savaş-barış, askerî teşkilat, silah-teçhizat ve askerî alametler gibi konular değerlendirilmiştir. Çalışmada askerlik ve savaş konusu bütünen incelenmiş, savaş hazırlıklarıyla başlayan süreç savaş sona erene kadar ayrıntılı bir kompozisyon şeklinde ele alınmıştır. Türk milletinin askerlik anlayışı ve askerliğe verdiği önem, şiir örneklerinden hareketle ortaya koyulmuştur.

In this study, a comprehensive research has been carried out on military terms in selected divans from the beginning of classical Turkish poetry up to the end of the 16th century. The military terms in the selected divans have been subjected to a specific classification and examined. While selecting the divans, the divans of soldier poets and of poets who were famous in the period they lived in were preferred. The military history of the Turkish nation, full of heroism and victories, has been mentioned by referring to literary poetic texts. In this study, which consists of four sections, topics such as war peace, military organization, weapons-equipment, and military insignia have been evaluated. The subject of soldiering and warfare has been examined as a whole, and the process beginning with war preparations has been handled in the form of a detailed composition until the war ends. The Turkish nation’s understanding of soldiering and the importance given to military service have been revealed based on examples from poetry.
Keywords: askerlik; barış; Barış şiiri, Türk; military service; Osmanlı Edebiyatı; Ottoman Literature; peace; Peace poetry, Turkish; poetry; Savaş; Savaş şiiri, Türk; silah; şiir; Turkish poetry; Türk şiiri; War; War poetry, Turkish; weapon